PERAN GURU DALAM MEMBENTUK PEMBELAJARAN SOSIAL DAN BERMAIN BERMAKNA UNTUK ANAK USIA DINI - Utia Virli Susanti; Nunung Nuryati; Deden HMS (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: In the context of Islamic Religious Education (PAI), the challenges in teaching are increasing. In Vocational High Schools, the subjects that are more emphasized or aimed at are special vocational subjects, so there are many models and methods that vary more to vocational subjects. The application of Islamic Religious Education learning usually uses less varied methods in the form of conventional methods such as lectures, memorization, and discussions. In this case, Islamic Education learning in vocational schools began to use technology based on artificial intelligence. This research aims to analyze the application of artificial intelligence-based adaptive learning technology in Islamic Religious Education (PAI) subjects at SMK Negeri 2 Kraksaan as well as student learning motivation and convenience for educators in the learning process.  The method used is a descriptive qualitative approach, with the type of case study research. Data were collected through interviews, observations and documentation of PAI teachers and students. The data showed that ChatGPT and Canva AI were the most frequently used platforms. ChatGPT is used to organize materials, answer student questions, create practice questions, and become an option to find references more quickly. Canva AI is used to create visual learning aids, such as infographics and creative presentations resulting in the presentation of interesting data in the form of visual designs. The use of these two platforms has been proven to increase students' interest in learning and help teachers prepare materials more efficiently. However, there are still some challenges, such as teachers and students need to be more careful with the validity of the information obtained, digital literacy training for teachers, and the need for supervision so that students do not rely too much on AI. Keywords: Artificial Intelligence, Adaptive Learning Technology, Islamic Religious Education. Abstrak: Dalam konteks Pendidikan Agama Islam (PAI), tantangan dalam pengajaran semakin meningkat. Pada Sekolah Menengah Kejuruan mata pelajaran yang lebih ditekankan atau yang lebih ditujukan adalah mata pelajaran khusus kejuruan, sehingga banyak model dan metode yang bervariatif lebih kepada mata pelajaran kejuruan. Penerapan pembelajaran Pendidikan Agama Islam biasanya menggunakan metode yang kurang bervariatif berupa metode konvensional seperti ceramah, hafalan, dan diskusi. Dalam hal ini pembelajaran PAI di SMK mulai menggunakan teknologi berbasis artifical intelligence. Melalui penelitian ini bertujuan untuk menganalisis penerapan teknologi pembelajaran adaptif berbasis kecerdasan buatan (artificial intelligence) pada mata pelajaran Pendidikan Agama Islam (PAI) di SMK Negeri 2 Kraksaan serta motivasi belajar siswa dan kemudahan bagi pendidik dalam proses pembelajaran. Metode yang digunakan adalah pendekatan kualitatif deskriptif, dengan jenis penelitian studi kasus. Data dikumpulkan melalui wawancara, observasi dan dokumentasi terhadap guru PAI dan siswa. Dari data tersebut dapat menunjukkan bahwa ChatGPT dan Canva AI adalah platform yang paling sering digunakan. ChatGPT digunakan untuk menyusun materi, menjawab pertanyaan siswa, membuat soal Latihan, dan menjadi pilihan untuk mencari referensi dengan lebih cepat. Canva AI digunakan untuk membuat alat bantu pembelajaran visual, seperti infografis dan presentasi kreatif sehingga menghasilkan penyajian data yang menarik dalam bentuk desain visual. Penggunaan kedua platform ini telah terbukti dapat meningkatkan minat belajar siswa dan membantu guru menyiapkan materi dengan lebih efisien. Namun, masih terdapat beberapa tantangan yaitu guru dan siswa harus lebih berhati-hati dengan kevalidan informasi yang didapat, pelatihan literasi digital kepada guru, dan perlunya pengawasan agar siswa tidak terlalu bergantung pada AI. Kata Kunci: Artificial Intelligence, Teknologi Pembelajaran Adaptif, Pendidikan Agama Islam.